2015
DOI: 10.1111/jace.13983
|View full text |Cite
|
Sign up to set email alerts
|

Raman Vibrations, Domain Structures, and Photovoltaic Effects in A‐Site La‐Modified BiFeO3Multiferroic Ceramics

Abstract: Micro-Raman spectroscopy, X-ray diffraction, high-resolution transmission electron microscopy (TEM), oxygen vacancies, synchrotron X-ray absorption spectroscopy, magnetizations, optical band gaps, and photovoltaic (PV) effects have been studied in (Bi 1 -x La x )FeO 3 (BFO100xL) ceramics for x = 0.0, 0.05, 0.10, and 0.15. XRD, Raman spectra, and TEM confirm a rhombohedral R3c symmetry with the tilted FeO 6 oxygen octahedra in all compounds. The low-frequency Raman vibrations become broader and shift toward hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Linear antiferromagnetic behavior and electric leakage have limited BiFeO 3 for electromagnetic applications. A-site substitutions of rare-earth elements onto the BiFeO 3 perovskite cell have been employed to enhance ferromagnetic, ferroelectric, and photovoltaic responses [8][9][10][11]. A-site substitutions of alkaline earth metal elements in BiFeO 3 , i.e., (Bi 1-x A x ) FeO 3 (A = Ca, Sr, Ba), have also demonstrated an improvement of magnetic and ferroelectric properties [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Linear antiferromagnetic behavior and electric leakage have limited BiFeO 3 for electromagnetic applications. A-site substitutions of rare-earth elements onto the BiFeO 3 perovskite cell have been employed to enhance ferromagnetic, ferroelectric, and photovoltaic responses [8][9][10][11]. A-site substitutions of alkaline earth metal elements in BiFeO 3 , i.e., (Bi 1-x A x ) FeO 3 (A = Ca, Sr, Ba), have also demonstrated an improvement of magnetic and ferroelectric properties [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly decreased average grain sizes were also observed in (Bi 1Àx La x )FeO 3 ceramics with increasing La. 14 The minimal grain size occurs in BFO14Sm may result from the structural instability as the system approaches the MPB. It was suggested that the grain size is associated with oxygen vacancies which can enhance ion migration to cause grain growth during the sintering process.…”
Section: Introductionmentioning
confidence: 67%
“…BFO10Sm, BFO12Sm, BFO14Sm, BFO16Sm, and BFO20Sm represent compounds of x = 0.10, 0.12, 0.14, 0.16, and 0.20, respectively. Similarly decreased average grain sizes were also observed in (Bi 1− x La x )FeO 3 ceramics with increasing La . The minimal grain size occurs in BFO14Sm may result from the structural instability as the system approaches the MPB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations